2019
DOI: 10.22435/hsr.v22i3.1304
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Distribusi Tenaga Kesehatan (Dokter Perawat Dan Bidan) Di Indonesia Pada 2013 Dengan Menggunakan Gini Index

Abstract: Equal distributions of physicians, nurses and midwives are the successful key to achieve the 12 public health indicators set by the World Health Organization. This study is to measure physicians, nurses and midwives inequality in Indonesia, 2013. Data for health workforce are obtained from routine data by the Board for Development and Empowerment of Human Resources for Health, 2013, and population data from Appendix 1 Books Code and Region Administration Data by Province, districs/cities and all Indone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
0
8
0
4
Order By: Relevance
“…In Indonesia, this pattern is also seen among other health professionals. An analysis in 2019 of general mixed health workforce distribution (physicians, nurses and midwives) using the Gini Index in Indonesia found that the number of physicians and nurses was concentrated in the capital of provinces or other big cities in the province [48]. Since 2015, the Ministry of Health of Indonesia has formulated the Nusantara Sehat programme for special recruitment to recruit health workers, including pharmacists, to work in community health centres in remote areas [49].…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, this pattern is also seen among other health professionals. An analysis in 2019 of general mixed health workforce distribution (physicians, nurses and midwives) using the Gini Index in Indonesia found that the number of physicians and nurses was concentrated in the capital of provinces or other big cities in the province [48]. Since 2015, the Ministry of Health of Indonesia has formulated the Nusantara Sehat programme for special recruitment to recruit health workers, including pharmacists, to work in community health centres in remote areas [49].…”
Section: Discussionmentioning
confidence: 99%
“…Like other low-and lower-middle-income nations, the city tends to have a more significant health worker density. 23,[34][35][36][37][38][39][40][41][42] While still skewed, the midwife and nurse ratios are less severe. 43 This finding is consistent with other research that found an uneven distribution of the total health workforce between rural and urban areas.…”
Section: Decomposition Of Inequitymentioning
confidence: 99%
“…13 Penelitian dengan melihat distribusi tenaga kesehatan (dokter, bidan dan perawat) menyatakan bahwa Nusa Tenggara memiliki ketimpangan tenaga kesehatan yang tertinggi dibandingkan regional lainnya. 14 Meskipun ada kebijakan penempatan tenaga kesehatan di Indonesia menggunakan sistem pegawai tidak tetap (PTT) untuk tenaga medis dokter dan dokter gigi, distribusinya masih tidak merata khususnya di daerah terpencil. 13 Distribusi tenaga medis gigi di Indonesia masih tidak merata karena adanya perbedaan yang besar dalam jumlah tenaga medis gigi antar pulau.…”
Section: Pembahasanunclassified